Short Communication: Vegetation and bird diversity in Pesanggrahan's lowland tropical forest, Malang, Indonesia - FATCHUR ROHMAN; NAILUL INSANI; PURWANTO PURWANTO; AGUS DHARMAWAN; INDRA FARDHANI; FARID AKHSANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rohman F, Insani N, Purwanto, Dharmawan A, Fardhani I, Akhsani F. 2023. Short Communication: Vegetation and bird diversity in Pesanggrahan's lowland tropical forest, Malang, Indonesia. Biodiversitas 24: 6169-6176. Universitas Negeri Malang proposes the designation of Pesanggrahan Forest as a Forest Area with a Specific Purpose or Kawasan Hutan dengan Tujuan Khusus (KHDTK). This study investigated plant and bird communities in the lowland tropical forest of Pesanggrahan. We observed 31 tree species, with Teak being the most dominant, with a medium level of diversity (H': 1.67) and an uneven distribution (E: 0.48). There were 104 species of shrubs and forest floor plants with a high diversity (H': 3.45) and an even distribution (E: 0.74) and 49 bird species, with some being protected by the Regulation of the Ministry of Environment and Forestry and listed as "vulnerable" or "near threatened" by International Union for Conservation of Nature (IUCN). These findings highlight the importance of the study site for conserving these species and their habitats. The interaction between plants and birds in Pesanggrahan's lowland tropical forest could be preserved by further investigation. This study can serve as preliminary data for future research on the interaction between the plant and bird species in this forest. Therefore, the designation of the forest as a protected area, or KDTK, would help conserve this habitat as one of the last remaining lowland forests on Java Island.